Implication of platelets and complement C3 as link between innate immunity and tubulointerstitial injury in renal vasculitis with MPO-ANCA seropositivity - Baier, Eva; Tampe, Désirée; Kluge, Ingmar Alexander; Hakroush, Samy; Tampe, Björn (Frontiers in Immunology, 2022)
Introduction: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a potentially life-threatening systemic small-vessel vasculitis that is characterized by pauci-immune glomerulonephritis, depicting in turn a major denominator of AAV mortality. It is well established that AAV patients feature an increased risk of developing thrombotic events, and platelets are activated in AAV patients being triggered by the alternative complement pathway. Platelets guard vessels integrity and initiate thrombus formation in response to endothelial damage, further constituting a triangular interconnection with the activation of neutrophils and the complement system. We here aimed to systematically assess the relevance of platelet counts and systemic complement system activation regarding distinct histopathological lesions in ANCA-associated renal vasculitis. Methods: A cohort of 53 biopsy-proven cases of ANCA-associated renal vasculitis were retrospectively enrolled in a single-center observational study. Univariate and multivariate regression analysis was performed to identify parameters associated with platelet counts in ANCA-associated renal vasculitis compared to disease controls. Finally, the relevance of platelets for disease course and recovery was assessed by survival analysis. Results: Lower platelet counts correlated with markers of kidney injury including eGFR loss (p=0.0004) and lower complement C3 levels (p=0.0037). Multivariate and subgroup analysis revealed that this association was only present in the subgroup with MPO-ANCA seropositivity (eGFR loss: p=0.0009, lower C3: p=0.0032). While lower platelet counts correlated with kidney injury in the PR3-ANCA subgroup (eGFR loss: p=0.0272), we did not observe an independent association with complement C3 levels (p=0.4497). Independent of any glomerular lesion, lower platelet counts correlated with interstitial fibrosis (p=0.0313), tubular atrophy (p=0.0073), and tubulitis in areas of interstitial fibrosis and tubular atrophy (p=0.0033). Finally, we observed significant differences with increased requirement of kidney replacement therapy (KRT) or death in the subgroup below median platelet counts (HR: 4.1, 95% CI: 1.6-10, p=0.0047), associated with a lower probability of discharge and prolonged hospitalization in this subgroup (HR: 0.5, 95% CI: 0.3-0.9, p=0.0113). Conclusion: Based on our observation that an association between platelets and complement system activation is only observed in the MPO-ANCA subgroup, this could implicate that platelets and complement C3 link innate immunity to tubulointerstitial injury in the presence of MPO-ANCA autoantibodies.